2020
DOI: 10.3390/nu12041192
|View full text |Cite
|
Sign up to set email alerts
|

Bus Stops Near Schools Advertising Junk Food and Sugary Drinks

Abstract: Children rarely understand the full extent of the persuasive purpose of advertising on their eating behaviours. Addressing the obesogenic environments in which children live, through a quantification of outdoor advertising, is essential in informing policy changes and enforcing stricter regulations. This research explores the proportion of bus stop advertisements promoting non-core food and beverages within walking distance (500 m) from schools in Auckland, New Zealand while using Google Street View. Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
0
29
1
Order By: Relevance
“…Of the 36 included studies, 28 reported on the prevalence of unhealthy advertising in outdoor spaces or on publicly owned assets 33–60 ; two reported associations between outdoor marketing and consumption of unhealthy food 6,61 ; one reported associations between outdoor advertising and the school food environment 58 ; one reported outdoor advertising and neighborhood level obesity rates 62 ; two reported on policy options for regulating unhealthy food marketing in outdoor environments 63,64 ; two reported on public opinions towards marketing regulation 65,66 ; and one study reported an evaluation of Chile’s Law of Food Labeling and Advertising 67 . A detailed description of all included studies from the academic literature is reported in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 36 included studies, 28 reported on the prevalence of unhealthy advertising in outdoor spaces or on publicly owned assets 33–60 ; two reported associations between outdoor marketing and consumption of unhealthy food 6,61 ; one reported associations between outdoor advertising and the school food environment 58 ; one reported outdoor advertising and neighborhood level obesity rates 62 ; two reported on policy options for regulating unhealthy food marketing in outdoor environments 63,64 ; two reported on public opinions towards marketing regulation 65,66 ; and one study reported an evaluation of Chile’s Law of Food Labeling and Advertising 67 . A detailed description of all included studies from the academic literature is reported in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported on outdoor advertising specifically in areas surrounding schools. These studies, undertaken in various countries (Australia, 44,52,53 New Zealand, 39,42,46,49,58 Canada, 57 the USA, 41,43 and Manila, The Philippines, and Ulaanbaatar, Mongolia 45 ), consistently showed that unhealthy food and beverage advertising is prevalent in areas around schools. For example, one Australian study of advertisements within a 500-m radius of primary schools in Sydney and Wollongong found that 80% of food and beverage advertisements were promoting unhealthy food, beverages and alcohol.…”
Section: Prevalence Of Unhealthy Food Advertising In Outdoor Environments or On Publicly Owned Assetsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, no recommendations for an optimal proportion for resampling exist. Precedents in child health and environment literature include Huang, Brien [83] physically confirming a random 10% selection of bus stops in a study using Google Street View to measure outdoor advertising around schools, and Vandevijvere, Sushil [84] randomly selecting 1% of 8403 geocoded food outlets and confirming details via telephone; however, the authors are unaware of this occurring with specific regard to physical activity destinations.…”
Section: Discussionmentioning
confidence: 99%
“…In children’s health geographies research, GSV has been used to measure obesogenic advertising in children’s neighbourhoods [ 53 ] and on bus stops around schools [ 54 ]. This growing area of research has demonstrated the utility of GSV to measure environmental features in relation to health outcomes.…”
Section: Introductionmentioning
confidence: 99%